2016
DOI: 10.4137/bic.s33376
|View full text |Cite
|
Sign up to set email alerts
|

BMI1: A Biomarker of Hematologic Malignancies

Abstract: BMI1 oncogene is a catalytic member of epigenetic repressor polycomb group proteins. It plays a critical role in the regulation of gene expression pattern and consequently several cellular processes during development, including cell cycle progression, senescence, aging, apoptosis, angiogenesis, and importantly self-renewal of adult stem cells of several lineages. Preponderance of evidences indicates that deregulated expression of PcG protein BMI1 is associated with several human malignancies, cancer stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 153 publications
(137 reference statements)
4
41
1
Order By: Relevance
“…In this study, we focused on the stemness factor BMI1 in lung cancer. We found that knockdown of BMI1 blocked LAC cell migration, invasion, chemo-resistance, and tumor initiation in vitro and in vivo (Figure 1 and 4E), confirming the previous recognition of BMI1 as a stemness regulator in cancer (6-9). Accordingly, targeting BMI1 with BI-44 suppressed LAC tumor formation and progression in pre-clinical model (Figure 6).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we focused on the stemness factor BMI1 in lung cancer. We found that knockdown of BMI1 blocked LAC cell migration, invasion, chemo-resistance, and tumor initiation in vitro and in vivo (Figure 1 and 4E), confirming the previous recognition of BMI1 as a stemness regulator in cancer (6-9). Accordingly, targeting BMI1 with BI-44 suppressed LAC tumor formation and progression in pre-clinical model (Figure 6).…”
Section: Discussionsupporting
confidence: 87%
“…BMI1 gene amplification or protein overexpression has also been found in various cancer types (7). BMI1 expression has been linked to the promotion of stemness properties of tumor cells, including to tumor initiation, cell proliferation, epithelial-mesenchymal transition (EMT), invasion, repression of apoptosis or senescence, and drug resistance (6-9). In lung cancer, however, the role of BMI1 has not been fully characterized.…”
Section: Introductionmentioning
confidence: 99%
“…Silencing of HOTAIR inhibited cell viability and induced G1-phase arrest by stimulating miR-218 expression. Inhibition of HOTAIR also activated expressions of P16 (INK4a) and P14 (ARF), the main downstream targets of miR-218 and 2 tumor suppressor genes, by enhancing miR-218 and suppressing B lymphoma Mo-MLV insertion region 1 homolog (Bmi-1), a member of the polycomb-group gene family [41], resulting in the inhibition of tumorigenesis in HCC [42]. In addition, HOTAIR increased the migration and invasion of HCC cells by inhibiting the expression of RNA-binding motif protein 38 [43].…”
Section: Hotair In Hepatocellular Carcinomamentioning
confidence: 99%
“…LPS-activated murine splenic B cells were transduced with pools of retroviral particles encoding genes associated with tumor transformation namely human MYC [8,9], BCLXL [10,11], hTERT [12], BMI1 [13,14], and activated HRAS (HRAS-V12) [15]. The transcription factor IRF4 [4, 6, 16,17] was also included due to its role in B-to plasma cell differentiation [18,19].…”
Section: Identification Of Gene Combinations Causing Transformation Omentioning
confidence: 99%